A sweet year : Jewish celebrations and festive recipes for kids and their families - Nathan, Joan (Alfred A. Knopf, 2024)
"In Jewish tradition, holidays are a time for family and feasting, and for Joan Nathan, nothing embodies the holiday spirit more than cooking delicious festive favorites with friends and loved ones. When her own children were young, Nathan published the first version of this book, which covers nine Jewish holidays and includes step-by-step instructions for kids and their families to prepare accessible feasts. Now she updates a beloved go-to resource for her grandchildren's generation (Out with the Pot Roast! In with the Tahini Shakes!) and adds a heaping helping of new recipes. Included are dishes old and new, traditional and novel, and mouthwatering recipes that everyone will enjoy, from Moroccan Apricot Chicken and Chicken Schnitzel Tenders to Mushroom Kreplach Dumplings and Veggie Quiche. Included are essays on the history of Jewish holidays, instructions for how to celebrate them, and craft activities such as making challah covers and candlesticks. Here are also personal essays on how Nathan's family celebrates the holidays and various menus that can be mixed and matched. For young chefs, recipes also specify the ingredients, equipment, and steps suitable for children to do both by themselves or with adults. This charming book is the comprehensive guide to Jewish holidays and celebrations, and it will help make memories that will last a lifetime. Included are recipes such as: *Rainbow-Colored Challah *Bagels with Apple and Cream Cheese Spread* Shakshouka *Banana strawberry pancakes *Fruit Noodle Kugel *Pasta with Pesto and Vegetables *Potato Latkes *Apple honey cupcakes *Date Tahini Banana Milkshake"--